2014
DOI: 10.6007/ijarppg/v1-i1/920
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Intelligence Influence on Employee Engagement Sustainability in Kenyan Public Universities

Abstract: Organizations the world over face challenges today which require reforms in the management

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 1 publication
1
8
0
1
Order By: Relevance
“…Mwangi in her research in 2014 points out that she observed an increasing competition in the university and more challenges with recruiting and also retaining qualified academic staff. She adds also that we can observe increased demands on grants and funding [60]. The problem with research funding of the research especially on PhD level was also observed by Horta [61].…”
mentioning
confidence: 77%
“…Mwangi in her research in 2014 points out that she observed an increasing competition in the university and more challenges with recruiting and also retaining qualified academic staff. She adds also that we can observe increased demands on grants and funding [60]. The problem with research funding of the research especially on PhD level was also observed by Horta [61].…”
mentioning
confidence: 77%
“…The drivers of EE investigated by Mwangi (2014) in Kenyan Universities are on areas of strategy or practice that frequently have an impact on commitment (engagement) which employees will generally respond positively. EI through self and social awareness and self and relationship management areas apparently affected and influence employee engagement mostly through vision, direction, company efficiency, and ethics.…”
Section: Emotional Intelligence and Employee Engagementmentioning
confidence: 99%
“…To improve the productivity of the organizations, many soft skills have become essential for employees to nurture and develop. Emotional intelligence is one of them (Mwangi, 2014). It is one of the prominent research areas of today's world (Goleman, Boyatzis, and McKee, 2013).…”
Section: Background To the Studymentioning
confidence: 99%